Tax competitiveness and business R&D expenditures: do taxes matter for innovation? - Hunady, Jan; Demeova, Eleonora (Business, Management and Economics Engineering, 2026)
Purpose – tax policies can be seen as one of the factors potentially affecting firms’ investment decisions and innovation. The paper examines the relationship between tax competitiveness and business Research and Development (R&D) expenditures across EU countries. Specifically, it analyses the tax rules governing corporate taxation in EU countries.  Research methodology – based on a combination of data from several databases (International Tax Competitiveness Index, OECD, and Eurostat) – we comprehensively examined the relationship. Using cluster analysis and PCA on cross-sectional data, we identified countries with similar tax competitiveness in relation to business R&D expenditures. Subsequently, we identified the effects of tax policy instruments and tax competitiveness on business R&D by using panel regression models (fixed effects and general method of moments).Findings – our results suggest that countries that are very similar in terms of tax competitiveness and the structure of individual tax elements (especially the Baltic countries) also achieve relatively low levels of R&D spending. While we get mixed results on R&D tax credits as a standalone R&D factor, tax competitiveness in general is significantly associated with business R&D expenditures in EU countries. The results also indicate the importance of tax instruments, which are hitherto less examined within the context of business innovation, such as tax depreciation rules.Research limitations – the size and geographical focus of the sample used in the analysis may limit general applicability and comparability with some previous studies based on datasets from different countries.Practical implications – the results are discussed within the current context of policies sup- porting innovation, and several policy recommendations have been highlighted. They help to guide more effective tax policies to boost business R&D and innovation.Originality/Value – there are only a few up-to-date empirical studies examining the effects of tax competitiveness on business R&D. Unlike prior studies, this paper analyses the relationship using a combination of quantitative techniques and classifies countries into clusters based on their tax competitiveness. The findings highlight the impact of overlooked aspects, such as tax depreciation rules.